Statistical Testing on Basic Science Practical on Students’ Performance in Ilorin-East LGA, Kwara State - Abidoye, Florence Omosholape; Abidoye, Adekunle Omotayo (Universitas Pendidikan Indonesia Kampus Serang, 2024)
It is urgent to address a systematic and objective approach to evaluating students’ practical skills. Exceptionally, current subjective assessment methods for students’ practical performance are to be provided with a more objective evaluation. Hence the study investigated the statistical testing on Basic Science practical on students’ academic performance in students in Ilorin East, Kwara State, Nigeria. The study was a descriptive research survey type. 120 students were sampled in secondary schools in Ilorin East LGA using a purposive sampling technique. The researchers designed a questionnaire was used to accumulate information from respondents. Data collected were analyzed using percentage, mean, frequency count, independent t-test, and ANOVA at 0.05 alpha significance level. The findings revealed that Basic Science practical has a great influence on school students' academic performance and also on the level of understanding and retention capabilities of students but there was no significant influence on students’ academic performance based on gender as well as class size. Also, student’s academic performance in Basic Science was not significantly influenced by gender or class size partially. It is recommended that all Basic Science teachers should engage students more in practical activities than the theory aspect to facilitate better understanding among the students.